Assessing municipal resource allocation and utilization for nutrition. - Manandhar, Shraddha. (Tufts University. Tisch Library., 2020)
This presentation aims to explore factors affecting allocation and utilization decisions of local government, particularly those which are actionable and affect investments for nutrition specific and nutrition sensitive activities.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy